Uncertain longevity and investment in education - Eytan Sheshinski (Center for Economic Studies and ifo Institute (CESifo), 2009)
It has been argued that increased life expectancy raises the rate of return on education, causing a rise in the investment in education followed by an increase in lifetime labor supply. Empirical evidence of these relations is rather weak. Building on a lifecycle model with uncertain longevity, this paper shows that increased life expectancy does not suffice to warrant the above hypotheses. We provide assumptions about the change in survival probabilities, specifically about the age dependence of hazard rates, which determine individuals' behavioral response w.r.t. education, work and age of retirement. Comparison is made between the case when individuals have access to a competitive annuity market and the case of no insurance.
Keywords: D11; D91; E21; G23; 330; longevity; survival functions; education; work; age of retirement; annuities; Bildungsinvestition; Bildungsverhalten; Lebenszyklus; Sterblichkeit; Arbeitsangebot; Altersgrenze; Private Rentenversicherung; Theorie